ESBL DETERMINATION AND ANTIBACTERIAL DRUG RESISTANCE PATTERN OF KLEBSIELLA PNEUMONIAE AMONGST PATIENTS AT PIMS ISLAMABAD - Khan, Jafar; Naz, Noor; AbdEl-Salam, Naser M.; Tabassum, Nayab Anum; Hussain, Hidayat; Ullah, Riaz (African Journal of Traditional, Complementary and Alternative Medicines, 2015)
Background: A number of life threatening infections due to various bacterial pathogens are major cause of death in Pakistan. In a situation like the other developing countries, there is a general increase in the drug resistance due to the irrational use of the antibiotics. The present study was carried out to evaluate the prevalence and development of resistance in Klebsiella pneumoniae against commonly used antibiotics. Methods and Materials: A total of 200 samples from different wards of the hospitals were received by the pathology laboratory of Pakistan Institute of Medical Sciences, Islamabad, which comprised of urine 65, blood 50 and other miscellaneous samples from various sources. Klebsiella pneumoniae was isolated and characterized using morphological, cultural, and biochemical methods and were further confirmed by using commercially available API 20E kit. The isolates were subjected to culture sensitivity test using Kirby Bauer disc diffusion method. Results: The organism was found to be the most prevalent Gram-negative bacilli. K. pneumoniae showed highest resistance against coamoxiclav and cephalosporins. Conclusion: The study revealed that ESBL producing strains were resistant to most of the beta-lactam antibiotics. This trend therefore has become a significant problem and can be controlled with continued surveillance or monitoring for rationally improved antibiotics usage, in order to prevent the drug resistance and re-emergence of infection.